Add-on sirolimus for the treatment of mild or moderate systemic lupus erythematosus via T lymphocyte subsets balance - Min Shi; Lin Yang; Jun Ma; Xiaoping Wang; Lu Jin; Meng Ding; Shaoxin Cui; Fei Chang; Hongtao Jin; Aijing Liu; Jinwen Zhao; Jingjing He; et al. (Lupus Science and Medicine)
Objective The efficacy of sirolimus in treating severe or refractory systemic lupus erythematosus (SLE) has been confirmed by small-scale clinical trials. However, few studies focused on mild or moderate SLE. Therefore, in this study we elucidated clinical efficacy of add-on sirolimus in patients with mild or moderate SLE.Methods Data of 17 consecutive patients with SLE were retrospectively collected. SLE Disease Activity Index-2000 (SLEDAI-2K), clinical manifestation, laboratory data and peripheral T lymphocyte subsets with cytokines were collected before and 6 months after sirolimus add-on treatment. T cell subsets were detected by flow cytometry and cytokines were determined by multiplex bead-based flow fluorescent immunoassay simultaneously. Twenty healthy controls matched with age and sex were also included in our study.Results (1) The numbers of peripheral blood lymphocytes, T cells, T helper (Th) cells, regulatory T (Treg) cells, Th1 cells, Th2 cells and Treg/Th17 ratios in patients with SLE were significantly lower, while the numbers of Th17 cells were evidently higher than those of healthy control (p<0.05). (2) After 6 months of sirolimus add-on treatment, urinary protein, pancytopenia, immunological indicators and SLEDAI-2K in patients with SLE were distinctively improved compared with those before sirolimus treatment (p<0.05). (3) The numbers of peripheral blood lymphocytes, T cells, Th cells, Treg cells, Th2 cells and the ratios of Treg/Th17 in patients with SLE after treatment were clearly higher than those before (p<0.05). (4) The levels of plasma interleukin (IL)-5, IL-6 and IL-10 in patients with SLE decreased notably, conversely the IL-4 levels increased remarkably compared with pretreatment (p<0.05).Conclusions (1) Patients with SLE presented imbalanced T cell subsets, especially the decreased ratio of Treg/Th17. (2) Sirolimus add-on treatment ameliorated clinical involvement, serological abnormalities and disease activity without adverse reactions in patients with SLE. (3) The multi-target therapy facilitates the enhanced numbers of Treg cells, Treg/Th17 imbalance and anti-inflammatory cytokines, simultaneously, reducing inflammatory cytokines.